Micro-foaming of plant protein based meat analogues for tailored textural properties - Joël I. Zink; Liridon Zeneli; Erich J. Windhab (Current Research in Food Science, 2023)
Meat-like foods based on plant protein sources are supposed to be a solution for a more sustainable sustenance of the world population while also having a great potential to reduce the impact on climate change. However, the transition from animal-based products to more climate-friendly alternatives can only be accomplished when consumers' acceptance of plant-based alternatives is high. This article introduces a novel micro-foaming process for texturized High-Moisture Meat Analogues (HMMA) conferring enhanced structural properties and a new way to tailor the mechanical, appearance and textural characteristics of such products. First, the impact of nitrogen injection and subsequent foaming on processing pressures, temperatures and mechanical energy were assessed using soy protein concentrate and injecting nitrogen fractions in a controlled manner in the range of 0 wt% to 0.3 wt% into the hot protein melt. Direct relationships between related extrusion parameters and properties of extruded HMMAs were established. Furthermore, optimized processing parameters for stable manufacturing conditions were identified. Secondly, so produced HMMA foams were systematically analyzed using colourimetry, texture analysis, X-ray micro-tomography (XRT) and by performing water and Preprint submitted to Innovative Food Science and Emerging Technologies June 17, 2023 oil absorption tests. These measurements revealed that perceived lightness, textural hardness, cohesiveness and overrun can be tailored by adapting the injected N2 concentrations provided that the gas holding capacity of the protein matrix is high enough. Moreover, the liquid absorption properties of the foamed HMMA were greatly optimized. XRT measurements showed that the porosity at the center of the extrudate strands was the highest. The largest porosity of 53% was achieved with 0.2 wt% N2 injection, whilst 0.3 wt% N2 lead to destructuration of the HMMA foam structure through limited gas dispersion and wall slip layer formation. The latter can, nonetheless, be improved by adapting the processing parameters. All in all, this novel extrusion microfoaming process opens new possibilities to enhance the structural properties of plant-based HMMA and ultimately, consumers’ acceptance.